Making the most of meetings: An entry point for knowledge sharing - Staiger Rivas, Simone; Russell, N.; Hewlitt, A. (2005)
More effective sharing of the knowledge generated by agricultural research and development (R&D) will enhance global efforts to reduce poverty, hunger and environmental degradation. Major meetings provide a useful opportunity for introducing knowledge sharing (KS) attitudes, methods and tools to R&D organizations. Such events can promote awareness of new types of collegial relationships and foster more creative scientific collaboration. If they are to successfully perform these functions, however, the meeting organizers must plan carefully, identifying the KS techniques that are most appropriate to the defined objectives. Feedback mechanisms (before, during and after the event) are also required. While major meetings can be an entry point for KS into an organization, they will not necessarily lead to mainstreaming of the concept. It is important to incorporate KS into the whole information continuum; a process that includes internal and external communication channels and involves all the organization’s stakeholders. For KS to lead to organizational change and sustainable improvements in performance, top-level management must be committed and meeting results must be followed through.